Electrical Joule heating of cementitious nanocomposites filled with multi-walled carbon nanotubes: role of filler concentration, water content, and cement age. (16th November 2020) - Liebscher, Marco; Tzounis, Lazaros; Junger, Dominik; Dinh, Tin Trong; Mechtcherine, Viktor
Abstract: In the study at hand the Joule heating effect of electrically conductive cementitious nanocomposites filled with different loadings of multi-walled carbon nanotubes (MWCNTs) is investigated. Nanofiller dispersions were initially prepared via ultrasonication in deionized water (d-H2 O) utilising a commercial superplasticizer as surfactant. Electrically percolated nanocomposites were fabricated via shear mixing and subsequent casting into moulds. Storing the prepared samples under different humid conditions enabled explanation of the role of water content as well as cement age on Joule heating performance. All prepared specimens were investigated at ages of 3 d, 7 d and 28 d by applying two different DC bias voltages. Infrared-thermography (IR-T) images were recorded after 1 min, 5 min and 10 min in order to visualize the differences in the Joule heating effect as a function of time, keeping contact with the DC bias voltage. The observed results showed a significant dependency of the Joule heating effect on water content as well as on filler concentration. Moreover, increasing cement age provided more effective electrical heating. This work elucidates the complexity of the electrical heating phenomena occurring in cementitious/MWCNT nanocomposites via the well-known Joule heating effect because it contributes to the understanding of the underlying mechanism. The main parameters used and the corresponding results are envisaged to be applicable for large-scale, heatable concrete structures in future respecting buildings temperature, aerial control, de-icing, thermal management, and better energy efficiency, etc.